2017
DOI: 10.18632/oncotarget.v8i27
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: News on: Sphingosine kinase 2 inhibition synergises with bortezomib to target myeloma by enhancing endoplasmic reticulum stressby Wallington-Beddoe et al.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 5 publications
0
6
0
Order By: Relevance
“…This was achieved by upregulating the expression of PCK1. Further findings indicated that hsa_circ_0005986 functioned as a tumor suppressor in the progression of HCC (286). The expression of hsa_circ_0005986 was significantly downregulated in HCC tissues compared to healthy tissues.…”
Section: An Overview Of Circrnas In Cancermentioning
confidence: 85%
“…This was achieved by upregulating the expression of PCK1. Further findings indicated that hsa_circ_0005986 functioned as a tumor suppressor in the progression of HCC (286). The expression of hsa_circ_0005986 was significantly downregulated in HCC tissues compared to healthy tissues.…”
Section: An Overview Of Circrnas In Cancermentioning
confidence: 85%
“…EPCAM has been widely studied as a therapeutic target and a prognostic marker in various epithelial malignancies, including breast, ovarian, urothelial, and non-small cell lung carcinomas. Tayama et al found that high EPCAM levels correlated with chemotherapy resistance and poor prognosis in ovarian cancer patients; thus, targeting EPCAM is a potential promising approach to treat chemoresistant ovarian cancer 77. However, data from Woopen et al showed that EPCAM overexpression in EOC was significantly associated with improved OS ( P = 0.015) and an increased rate of response to platinum-based chemotherapy ( P = 0.048) 78.…”
Section: Discussionmentioning
confidence: 99%
“…Basic research identifying the role of the cyclin D-CDK4/6-Rb axis in G1 to S cell cycle transit, followed by translational and clinical studies in which this axis was linked to breast cancer progression and antiestrogen resistance ( 46 , 47 ), culminated in the development of CDKi’s currently used in combination with endocrine treatments for ER + HER2 negative breast cancer ( 48 ). CDK4/6 small molecule inhibitors currently used as an adjuvant to antiestrogen treatment include palbociclib, ribociclib, and abemaciclib.…”
Section: Cdki As An Adjuvant To Antiestrogen Therapymentioning
confidence: 99%